Decreased vitamin D levels in children with familial Mediterranean fever. (11th January 2014) - Anık, Ahmet; Çatlı, Gönül; Makay, Balahan; Abacı, Ayhan; Küme, Tuncay; Ünsal, Erbil; Böber, Ece
Abstract Objectives To determine the frequency of vitamin D deficiency in children with familial Mediterranean fever (FMF) and to investigate the factors associated with low vitamin D status. Design and methods Forty‐four patients with FMF and 39 age‐ and sex‐matched healthy controls were enrolled in this study. Demographic data, FMF symptoms, disease duration, time to delay for diagnosis, duration of follow‐up, disease severity score, MEFV gene mutation, cumulative colchicine dose, compliance to treatment and serum C‐reactive protein levels were recorded for each patient. Serum 25‐hydroxyvitamin D levels were measured by an original commercial kit based on chemiluminescent microparticle immunoassay (CMIA). Results The serum 25‐hydroxyvitamin D levels were significantly lower in FMF patients than the healthy controls (12.9 ± 3.6 and 16.3 ± 5.5 ng/mL, respectively, P = 0.001). Vitamin D levels were similar in patients homozygous for M694V and other genotypes (11.8 ± 3.7 and 13.2 ± 3.6 ng/mL, respectively, P = 0.21). Stepwise multiple linear regression analysis confirmed that the cumulative colchicine dose was the strongest independent variable correlating with vitamin D levels (r2 = 0.194, P = 0.001). Conclusion Our results suggest that serum 25‐hydroxyvitamin D levels are decreased in children with FMF. Cumulative colchicine dose appears to negatively affect vitamin D levels. The role of colchicine on vitamin D metabolism needs to be elicited.